2014
DOI: 10.1177/0169796x13504680
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus of Female Capital and North–South Labor Migration in Ghana

Abstract: The phenomenon of female head-load portaging in the large commercial cities of Southern Ghana has become a social canker. This article explores the role access to capital plays in the labor relocation of women from northern to Southern Ghana to engage in street head-load portaging, with the goal of examining the potential of microfinance to reverse this trend. Using a phenomenological study design and semi-structured interviews of 15 migrant women porters in Accra, the results revealed that lack of access to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…"Kayayei" is considered a small form of trading culturally understood as being women's work-head-load carriers are selfemployed, informal sector workers. These migrant adolescent girls carry loads of goods on daily basis on their heads in the commercial cities to enable them raise money to help improve their economic fortunes (Tufeiru, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Kayayei" is considered a small form of trading culturally understood as being women's work-head-load carriers are selfemployed, informal sector workers. These migrant adolescent girls carry loads of goods on daily basis on their heads in the commercial cities to enable them raise money to help improve their economic fortunes (Tufeiru, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alatinga (2019) reported that only 36% of migrant adolescent girl head porters were able to remit to their families back home, with amounts ranging between US$18.5-55.57 annually. In addition, the physical nature of their work and the poor circumstances under which these adolescent girls work and live expose them to several health risks including malaria, skin diseases, aches and pains, accidents, injuries, rape and unwanted pregnancies as well as physical abuse (Awumbila & Ardayfio-Schandorf, 2008;Tufeiru, 2014). Also, their low incomes may prevent them from enrolling onto contributory social protection schemes such as the NHIS, which aims to ensure equity and universal access to health care for the poor and protect them against the costs of illness (National Health Insurance Act, 2012(ACT 852), 2012.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [5] argues that the youth in Africa are always moving as they desire to migrate from rural areas to urban areas in search for better opportunities and greener pastures. In this regard, most rural dwellers in Africa, such as Morocco and Ghana, see ruralurban migration as a survival strategy to withstand harsh economic conditions in rural areas [5; 6].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of mostly women in head porting could be due to the fact that women from Ghana are used to head porting as they often carry goods from the farms to their homes and sometimes from the homes to the markets [3]. Irrespective of the proliferation of automobiles which has reduced the burden of women, most rural women still engage in head porting business as their main means of transport [4].…”
Section: Introductionmentioning
confidence: 99%